Safety and resource utilisation efficiency of semi-skeletonised versus skeletonised left internal mammary artery harvesting techniques: The BANGABANDHU study - Redoy Ranjan; Aziz Momin; Riyaz A. Kaba; Gie Ken-Dror; Sanjay Kumar Raha; Md Kamrul Hasan; Venkatachalam Chandrasekaran; Asit Baran Adhikary (PLoS ONE, 2025)
Background The ideal harvesting techniques of the left internal mammary artery (LIMA) for coronary artery bypass graft (CABG) are elusive. We assessed the safety and resource utilisation efficiency of semi-skeletonised LIMA harvesting techniques, focusing on length, harvesting time, and the number of Ligaclips used compared to skeletonised techniques within a single surgeon’s practice. Methods The BANGABANDHU (Bangladeshi Atherosclerosis Biobank AND Hub) study was an ambispective observational cohort that evaluated age- and sex-matched 2209 adult Bangladeshi isolated CABG population from 1st January 2015 to 31 January 2025. Univariate analysis observed the difference pattern in the dataset, while multivariate logistic regression (LR) analysis identified the independent variables associated with the advantage of semi-skelitonised LIMA. The area under the receiver operating characteristic (AUROC) curve demonstrated the goodness-of-fit of the prediction model. Results We evaluated 2209 age- and sex-matched adult isolated CABG patients (skeletonised LIMA; n = 1050 and semi-skeletonised LIMA; n = 1159) with identical comorbidities (EuroSCORE II, hypertension, diabetes, renal impairment, COPD, left main and multivessel coronary artery disease) between study groups (p > 0.05). LIMA harvest time (35.9 ± 5.5 vs 16.6 ± 3.9; p < 0.001) and number of used Ligaclip (23.6 ± 4.8 vs 11.7 ± 3.6; p < 0.001) were significantly higher in the skeletonised compared to the semi-skeletonised LIMA sample. Furthermore, an age and sex-adjusted multivariate logistic regression model found LIMA harvest time (odds ratio [OR] 0.067, 95% CI 0.01–0.39; p = 0.003) and number of used Ligaclip (OR 0.561, 95% CI 0.41–0.76; p < 0.001) significantly lower among semi-skeletonised LIMA techniques. Conclusion The semi-skeletonised LIMA technique is advantageous as it significantly reduces harvesting time and requires fewer Ligaclips compared to the skeletonised technique.